БЕЗПЕЧНЕ ВІДКЛЮЧЕННЯ ЕЛЕГАЗОВИХ ВИМИКАЧАІВ У ПОВІТРЯНИХ ЛІНІЯХ ЕЛЕКТРОПЕРЕДАЧІ - Шполянський, О.Г. (Інститут електродинаміки НАН України, Київ, 2021)
The paper analyses the transient currents during the energisation of a 750 kV overhead transmission line (OTL). The safety of OTL state after symmetrical and asymmetrical closing of the circuit breakers and technical feasibility of SF6 circuit breakers opening with time delay after their closing is substantiated. The necessity of transient processes simulation for analysing the characteristics of periodic and direct components of currents is shown. A method for determining of SF6 circuit breaker opening time delay for a set of states that may arise after the energisation of OTL is developed. References 13, tables 2, figures 5.